RpoN-dependent adaptation of burkholderia xenovorans LB400 for biodegradation and bioremediation of dibenzofuran / Noor Faizul Hadry Nordin - Noor Faizul Hadry, Nordin (2012)
Alternative sigma subunit-54 (RpoN) forms holoenzyme complex when associated with core RNA Polymerase (RNAP) to specifically recognise and initiate transcription of specific sets of genes in response to environmental stimuli. RpoN has important role in many major adaptive responses in bacteria and is involved in various physiological responses such as pathogenesis, quorum sensing and bioremediation. The main focus of this study is to gain insight into the role of alternative sigma factor-54 (RpoN) of Burkholderia xenovorans LB400 in degradation of dibenzofuran via biphenyl degradation pathway. Additionally, this study also investigated the ability of Burkholderia cenocepacia J2315 in utilisation of dibenzofuran. The single knockout mutants of rpoN genes were established using pKNOCK suicide vector series resulting two rpoN mutants of Burkholderia xenovorans LB400; NRPLB [(rpoN1 mutant) and NRP2LB (rpoN2 mutant)] and one rpoN mutant of Burkholderia cenocepacia J2315 [NRPJ (rpoN mutant)]. The physiological and metabolic responses analyses were conducted to differentiate the single-gene knockout mutants from their wildtype strains; Burkholderia xenovorans LB400 and Burkholderia cenocepacia J2315. The physiological response analysis demonstrated that the ability of the mutants NRPLB and NRP2LB to form biofilm were not affected with inactivation of rpoN genes. However, the biofilm formation in NRPJ was reduced indicating the involvement of rpoN gene in formation of biofilm in Burkholderia cenocepacia J2315. Inactivation of rpoN2 gene does not affect motility of NRP2LB (rpoN2 mutant). However, inactivation of rpoN1 gene significantly reduced motility of NRPLB (rpoN1 mutant). Metabolic response analysis shows that rpoN genes play an important role in utilisation of nitrogenous compound even though the effects are depending on the species of the nitrogen. The altered nitrogen utilisation profile when using ammonium, histidine, asparagines, nitrate, glutamine and alanine as sole nitrogen source in single-gene knockout mutants indicate that rpoN genes of Burkholderia xenovorans LB400 and Burkholderia cenocepacia J2315 are active and functional for nitrogen utilisation. The ability of Burkholderia xenovorans LB400 and Burkholderia cenocepacia J2315 in degrading orthosubstituted PCBs such as dibenzofuran was also determined. Degradation studies of dibenzofuran showed significant differences between wildtype Burkholderia xenovorans LB400, Burkholderia cenocepacia J2315 and their single-gene knockout mutants. Degradation rate was found higher in NRP2LB (rpoN2 mutant) compared to wildtype Burkholderia xenovorans LB400 but reduced significantly in NRPLB (rpoN1 mutant). This result was supported by gene expression analysis where RpoN-dependent bphA gene that encodes for biphenyl dioxygenase was highly expressed in NRP2LB (rpoN2 mutant) thus enhanced the degradation of dibenzofuran via biphenyl degradation pathway. This result indicates the important role of rpoN1 gene in Burkholderia xenovorans LB400 in degradation of dibenzofuran. Simple phytotoxicity assay showed that byproducts from degradation of dibenzofuran by wildtype Burkholderia xenovorans, NRPLB (rpoN1 mutant) and NRP2LB (rpoN2 mutant) is less toxic towards the test species compared to dibenzofuran. Furthermore, the degradation byproducts from NRP2LB (rpoN2 mutant) was able to enhanced the growth of Sorghum saccharatum compared to control (water).